Due contributi sulla scultura lignea per il prof. Jakšić - Matejčić, Ivan (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
The statue of angel candleholder is exhibited in the collection of the parish church of St. Blaise in Vodnjan. It originates from the church of St. Michael built in 1456 on the locality Banjole , between Vodnjan (Dignano) and Batvač (Valmadorso). It shows characteristics of the late Gothic Venetian art from the first half of 15th century. For almost 40 years Venetian woodcarver and sculptor Paolo Campsa (first mentioned in 1495, died in Venice 1541) managed a very productive workshop that delivered dozens of altars with reliefs and sculptures. Some of these artworks are in Croatia and a few of them have been presented only recently. Samo Štefanac wrote that reliefs of Virgin with a Child from Bale (Valle) and Štinjan (Stignano) were Campsa’s work, while I. Matejčić had a different opinion. The important detail for this wood carving workshop has been revealed on an inscription on the base of the central statue of a big altar in Mutvoran that is now completely visible. It states not only the name of the author, but also the year 1533. The altarpiece is in the process of restoration that has brought to light authentic polychromy of high quality. Some 40 years ago central statues from the main altar in the church Della Bastia in Isola della Scala were stolen, but with help of preserved photographs and remaining parts on the altar it is possible to recognize the work of the Campsa Bottega. Small reliefs with scenes from Christ’s childhood on predella explicitly resemble those from Motovun (Montona), Jelsa and Quinto di Treviso. New contributions and comparisons open possibilities for further assumptions about the roll different carvers had while the Bottega worked on big altarpieces.